Using Think-Pair-Share to Develop Students' Social and Emotional Competencies in Chemistry Learning - Yuli Rahmawati; Tri Hastuti Budi Utami; Muktiningsih Nurjayadi; Alin Mardiah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
The aim of this study was to analyze students' social and emotional competencies through the integration of Think Pair Share (TPS) and a Social and Emotional Learning (SEL) approach to topics related to Acids and Bases. Social and emotional learning (SEL) is the process through which children and adults understand and manage emotions, set and achieve positive goals, feel and show empathy for others, establish and maintain positive relationships, and make responsible decisions.. The study involved thirty-five 11th grade students in one of private school in Jakarta and was conducted between January and April, 2017. A qualitative methodology was employed to analyze students’ social and emotional competencies using interviews, classroom observations, reflective journals, and student worksheets. The application of a SEL approach was carried out by integrating it with a TPS strategy. In the Think stage students were given the opportunity to explore their understanding of acids and bases and to solve problems individually. In the Pair stage they could communicate their insights to the group, and in the Share stage they had occasion to present their group perspectives and respond to others. The five social and emotional competences found in this study were; self awareness, self management, social awareness, relationship management, and responsible decision making. Self awareness was demonstrated by understanding a student’s abilities, their needs, and their self- confidence. Self management was indicated by a student’s ability to manage pressure, plan strategies, and seek help. Social awareness competencies were analyzed through the development of students' attitudes to diversity and how they demonstrated care for friends. Relationship management competencies were identified by observing a student’s ability to manage friendships, how they overcame differences, and whether they provided assistance to each other. The responsible decision making competency was determined by observing how students made decisions when trying to solve a problem and whether they were able to plan a strategy when facing pressure. Whilst integrating SEL the researchers were challenged by the need to empower students, encourage teachers to stimulate students’ social and emotional competencies, and to manage time constraints. Integrating SEL into chemistry learning provided opportunities for students to develop their social and emotional competencies through independent thinking activities, group discussions, and presentations to their peers.